23 Impact of public access defibrillation on the long-term outcomes of cardiac arrest survivors. (26th April 2019) - Nehme, Z; Andrew, E; Bernard, S; Dyson, K; Smith, K
Abstract : Background: Little is known about the impact of public access defibrillation (PAD) on the long-term outcomes following out-of-hospital cardiac arrest (OHCA). We examine the impact of PAD on functional recovery and health-related quality-of-life in 12 month survivors of OHCA. Method: Between 2010 and 2016, adult OHCA survivors with an initial shockable rhythm were invited to participate in structured telephone interviews at 12 months post-arrest using the Glasgow Outcome Scale–Extended (GOSE), the EuroQol-5D (EQ-5D), and 12-Item Short Form (SF-12) health survey. Adjusted logistic regression was used to assess the effect of PAD on good functional recovery (GOSE ≥7) at 12 months. Results: Of the 1, 221 12 month survivors, 1036 (85.6%) participated in telephone interviews of which 144 (13.9%) were first shocked by PAD. When compared to patients first shocked by EMS, a higher proportion of patients shocked by PAD reported living at home without care (84.7% vs. 76.3%, p=0.02) and returning to work (83.3% vs. 71.5%, p=0.02). Although SF-12 mental component summary did not differ between groups, fewer patients shocked by PAD reported physical disability according to the SF-12 (35.7% vs. 45.3%, p=0.04). Best imaginable health status (an EQ-5D score of 1) was also reported more frequently in patients shocked by PAD (52.5% vs. 41.9%, p=0.02). After adjustment, PAD increased the odds of good functional recovery by 77% (adjusted odds ratio [AOR] 1.77, 95% CI: 1.16, 2.71; p=0.008). Conclusion: Cardiac arrest patients shocked by PAD experience better long-term outcomes and more often report living independently. Conflict of interest: None to declare. Funding: Dr. Nehme is supported by an early career fellowship (#1146809) from the National Health and Medical Research Council.